The dream for pre-primary - "Hunt,Roderick" (Oxford university press, 1986)
"The Dream" by Roderick Hunt is a whimsical story from the Oxford Reading Tree series. In this tale, the characters embark on an imaginative adventure as they explore the concept of dreams and what they can mean. Through vivid imagery and playful scenarios, they encounter fantastical elements that spark their creativity. The story encourages young readers to think about their own dreams and the power of imagination. With engaging illustrations and a charming narrative, it captivates children's interest while highlighting themes of exploration and wonder.
Keywords: Textbook